From Spoken Word to Playwriting - Agathe Faucourt; Jade Thomas (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2023)
Interview with Aleshea Harris, playwright, screenwriter and performer. The interview was conducted over Zoom on the 22nd of November, 2022.